Pemanfaatan Air Lindi Limbah Organik Rumah Tangga Sebagai Nutrisi Tanaman Dengan Sistem Hidroponik - Bimasri, John; Murniati, Nely; Warah, Warah (Universitas Dehasen Bengkulu, 2025)
Organic solid waste produces leachate and can pollute the environment. Leachate in agriculture can act as fertilizer, because it contains elements that plants need, such as nitrogen and phosphorus. Plant cultivation technology continues to develop, one of which is hydroponics. The obstacle faced in cultivating plants hydroponically is nutritional requirements. Leachate can be used as an AB-mix nutrient mixture to reduce production costs for hydroponic plant cultivation. Activities were carried out in Hamlet 6, Tambah Asri Village, Tugu Mulyo District, Musi Rawas Regency from July to August 2023 using counseling, demonstration and mentoring methods. The counseling was attended by 45 participants, mothers and young women in Dusun Enam, then as many as 8 groups consisting of 5 to 6 people carried out hydroponic cultivation with nutrients using leachate from household organic waste combined with AB-mix. The results of carrying out this activity can be concluded that household organic solid waste can be processed into leachate for fertilizer, and reduce environmental pollution. Leachate water provides nutrients for plants hydroponically, thereby reducing cultivation costs.